Análise de uma situação de aprendizagem para o ensino de coordenadas cartesianas - Aliano, Larissa Cristina (Universidade Federal de São Carlos, 2016)
This dissertation has main goal analyze the Learning Situation “Cartesian coordinates and transformations in the plane” of Material Support Curriculum of the State of São Paulo, Student notebook, submit a proposal of a didactic sequence to the topic and check their effectiveness. The motivation for choosing this theme came from a study made of the results of SARESP, which present a low performance in the abilities involving this subject. The work begins with a study of issues on Cartesian coordinates of SARESP and Brazil Test, and official documents as PCN and Curriculum Proposal of the State of São Paulo. They are also appreciated opinions of some researchers in the field of education on the teaching of mathematics. We also make a brief analysis of how textbooks address the issue. Then described the planning of the teaching sequence that includes the Student Notebook activities as well as its application in two classes of students in Year 8. In implementing the activities we organize students into pairs, so that they could develop problems more autonomy and less interference from the teacher. After the implementation of the activities, students were evaluated by a test similar to the SARESP with some questions drawn from these tests and others built for myself. Using the results presented by the students in the activities and evidence did an analysis of trial and error. At the end we can conclude that our work is validated, because the students have obtained satisfactory results in the assessment, showing that the learning situation applied in the format presented propose an appropriate outcome compared with SARESP. To validate our research follow in big steps, the methodology proposed by didactic engineering. This educational product is available so that teachers can use it directly in their classes.
Keywords: Ensino de coordenadas cartesianas; Situação de aprendizagem; Material de apoio ao currículo do estado de São Paulo; Teaching cartesian coordinates; Learning situation; Material support curriculum of the state of São Paulo; CIENCIAS EXATAS E DA TERRA::MATEMATICA